The prognostic value of the Barthel Index for mortality in patients with COVID-19: A cross-sectional study - Wang, Erchuan; Liu, Ao; Wang, Zixuan; Shang, Xiaoli; Zhang, Lingling; Jin, Yan; Ma, Yanling; Zhang, Lei; Bai, Tao; Song, Jun; Hou, Xiaohua (Frontiers in Public Health, 2023)
Objective This study aimed to analyze the association between the activity of daily living (ADL), coronavirus disease (COVID-19), and the value of the Barthel Index in predicting the prognosis of patients. Methods This study included 398 patients with COVID-19, whose ADL at admission to hospital were assessed with the Barthel Index. The relationship between the index and the mortality risk of the patients was analyzed. Several regression models and a decision tree were established to evaluate the prognostic value of the index in COVID-19 patients. Results The Barthel Index scores of deceased patients were significantly lower than that of discharged patients (median: 65 vs. 90, P < 0.001), and its decrease indicated an increased risk of mortality in patients (P < 0.001). After adjusting models for age, gender, temperature, pulse, respiratory rate, mean arterial pressure, oxygen saturation, etc., the Barthel Index could still independently predict prognosis (OR = 0.809; 95% CI: 0.750–0.872). The decision tree showed that patients with a Barthel Index of below 70 had a higher mortality rate (33.3–40.0%), while those above 90 were usually discharged (mortality: 2.7–7.2%). Conclusion The Barthel Index is of prognostic value for mortality in COVID-19 patients. According to their Barthel Index, COVID-19 patients can be divided into emergency, observation, and normal groups (0–70; 70–90; 90–100), with different treatment strategies.